Fifth Geometric-Arithmetic Index of Polyhex Zigzag TUZC6[m,n] Nanotube and Nanotori - Farahani, Mohammad Reza (JOURNAL OF ADVANCES IN PHYSICS, 2013)
Among topological descriptors, connectivity indices are very important and they have a prominent role in chemistry. The geometric-arithmetic index (GA) index is a topological index was defined as GA (G) in which degree of a vertex v denoted by dv. A new version of GA index was defined by A. Graovac et al recently, and is equale to GA (G) where GA (G) In this paper, we compute this new topological connectivity index for polyhex zigzag TUZC6[m,n] Nanotube and Nanotori.